THE IMPLEMENTATION PROMOTIONS OF TOURIST ATTRACTIONS GURUH GEMURAI WATERFALL OF DEPARTMENT OF TOURISM AND CULTURE KUANTAN SINGINGI DISTRICT - R. Tria Safitri; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Promotion is a way of communicating that is usually done in an organization whose purpose is to attract potential customers to buy products and services that are sold or offered. This study aims to determine the implementation of the promotion of Guruh Gemurai Waterfall Attraction by the Tourism and Culture Office of Kuantan Singingi Regency and analyze what are the inhibiting and supporting factors of the promotion. This study uses a qualitative method with a descriptive approach, the subject of this study is the Head of Department, Head of Marketing, Head of the Tourism and Culture Office of the Kuantan Singingi Regency. Data collection is done by interview, observation, and documentation. Data analysis conducted in this research is data reduction, data presentation, and drawing conclusions. The results of this study are the implementation of promotions carried out through 4 (four) techniques which include Advertising, Personal Selling, Sales Promotion, and Public Relations. But until now the results are still not good because there are still many promotions that have not been implemented and have not utilized the promotional media to the full. The supporting factors are usually done such as the presence of entertainment programs and attractions. And the inhibiting factors encountered in the implementation of this promotion are funds that are still very limited to carry out large-scale promotions and infrastructure problems and supporting facilities that are still lacking in Kuantan Singingi Regency. For this reason, in carrying out the promotion of Guruh Gemurai Waterfall Tourism Objects, it is expected to make maximum use of promotional media.Keyword : travel promotion, promotion techniques, waterfall